A method for obtaining elastic parameters of shale before and after water-rock interaction
By performing electron microscopy scanning and nanoindentation testing on small-sized rock samples, combining Gaussian model and multi-scale theory, the mechanical parameters before and after the action of mud shale water rocks are analyzed, and it is difficult to obtain mud shale low permeability in the existing technology. The problem of mechanical parameters achieves efficient and economical acquisition of mechanical parameters and supports drilling design.
Patent Information
- Application Number
- CN202010305635.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-04-17
AI Technical Summary
The prior art is difficult to accurately obtain the macromechanical parameters of mud shale with extremely low permeability before and after the action of water rocks, especially due to the evolution of micromechanical weak surfaces and core breakage due to the hydration, so effective macromechanical testing cannot be carried out.
By grinding, electron microscopy scanning and nanoindentation testing of small-sized rock cutting samples, combining mixed Gaussian model and multi-scale theory, the microstructure and physical phase mechanical parameters of the rock sample were analyzed, and the macroelastic parameters before and after the action of water rock were calculated.
It realizes the acquisition of mechanical parameters before and after the action of mud shale water rock without being restricted by rock sample size, avoiding the problem that mud shale standard rock sample is not easy to saturate and the divergence of experimental data, and provides The mechanical characteristic parameters of the formation rock sample in the entire well section are supported to support the drilling and completion scheme design.
Smart Images

Figure CN113533104B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rock mechanics, and in particular to a method for obtaining elastic parameters of shale before and after water-rock interaction based on rock microscopic characteristics. Background Art
[0002] Rock mechanics parameters are the basic parameters for many construction operations during drilling and development, and are also the basic basis for drilling and completion design and oil production operations such as wellbore stability analysis and hydraulic fracturing. The correctness of rock mechanics parameters is related to the correct formulation of construction plans and the safe implementation of construction. On the other hand, during the drilling and completion process, the bottom rock of the well will inevitably interact with the drilling fluid or fracturing fluid, which will change the mechanical properties of the rock surface. Accurately obtaining the mechanical parameters of the rock before and after the water-rock interaction is of great significance for guiding the drilling and completion design and evaluating the construction effect.
[0003] As a valuable resource, bottom hole cores are usually obtained through coring. The coring operation takes a long time, the coring rate cannot be fully controlled, and the coring operation is generally only for a specific reservoir section, and it is impossible to obtain cores from the entire section. However, the cuttings returned from the annulus during the drilling cycle are relatively sufficient, and cuttings from the entire section can be obtained. If sufficient bottom hole cuttings resources can be used to explore a method to obtain rock mechanical parameters by microscopic testing of small-sized cuttings, it will be of great significance.
[0004] Indentation testing is a simple and efficient means of evaluating the mechanical properties of materials. It can accurately and continuously measure the load-displacement data of the indenter, based on which the relevant mechanical parameters can be easily obtained. It is currently widely used in the study of the mechanical properties of metals, thin film coatings, composite materials and biological tissues. There is a promising prospect for applying indentation testing technology to the acquisition of mechanical parameters of rock materials and the evaluation of water-rock interactions.
[0005] The existing technologies for obtaining the mechanical parameters of rocks before and after water-rock interaction include the following technologies: First, using a rigid flat-bottomed indenter to test the mechanical properties of rocks. The diameter of the indenter in this method reaches 0.5mm to 2mm, and the test size is relatively large. In essence, it is still a macroscopic mechanical test of rocks; Second, using a macroscopic triaxial loading experimental device to test the water-rock interaction. Although this method can control the water temperature, water pressure and axial pressure of the rock sample when it is saturated with water, and can control the saturation time of the rock sample, this method is suitable for rock samples with higher permeability. For mudstone with extremely low permeability, it is difficult to achieve the effect of completely saturating the entire rock sample in a short time; Third, although some schemes can qualitatively measure the degree of damage to rocks caused by cement action, they cannot quantitatively analyze the specific mechanical parameters of rock samples before and after water-rock action.
[0006] At present, the study of the method of obtaining rock mechanical parameters before and after water-rock interaction has achieved certain results, but the experimental methods mostly use macroscopic rock mechanical tests. For shales with microscopic mechanical weak planes such as lamellae, hydration will cause the microscopic mechanical weak planes to evolve and form macroscopic cracks, resulting in core fragmentation, making it impossible to conduct macroscopic mechanical tests after water-rock interaction. Therefore, it is still necessary to explore starting from small-sized rock samples and using microscopic testing methods to conduct rock mechanical parameter research, in order to make up for the difficulties of insufficient macroscopic mechanical test samples and difficult to obtain experimental data, and provide data support for the design of drilling and completion plans. Summary of the invention
[0007] In order to solve the above technical problems, an embodiment of the present invention provides a method for obtaining elastic parameters of mudstone before and after water-rock interaction, the method comprising: grinding a mudstone sample to be evaluated and analyzing the rock mineral content; scanning the rock sample with an electron microscope, analyzing the distribution and content of each phase in the scanned image, and based on this, determining the volume unit representing the microstructure of the rock sample; performing a nanoindentation test on the rock sample according to the volume representative unit, establishing a load and displacement curve of each indentation point, and based on this, calculating the elastic parameters of each indentation point; soaking the ballasted rock sample in fluid, scanning the rock sample with an electron microscope and performing a nanoindentation test in turn after soaking, and calculating the elastic parameters of each indentation point after soaking; according to the elastic parameters of each indentation point before and after soaking, using a mixed Gaussian model, respectively identifying the phase category of each indentation point, and calculating the elastic parameter trend of each phase category before and after soaking; according to the elastic parameter trend, obtaining the macroscopic elastic parameters of the mudstone sample to be evaluated before and after soaking from the rock mineral content analysis result.
[0008] Preferably, the step of obtaining the macroscopic elastic parameters of the shale sample to be evaluated before and after immersion according to the elastic parameter trend and the rock mineral content analysis result includes: calculating the bulk modulus and shear modulus of the corresponding phase category according to the elastic parameter trend of each phase category before and after immersion from the Poisson's ratio of each phase category before and after immersion; based on the rock mineral content analysis result, according to the bulk modulus and shear modulus of each phase category before and after immersion, using a multi-scale theoretical homogenization method, cross-scale upgrading the microscopic phase elastic parameters to obtain the bulk modulus, shear modulus, elastic modulus and Poisson's ratio of the shale sample to be evaluated before and after immersion.
[0009] Preferably, in the step of identifying the phase category of each indentation point respectively using a mixed Gaussian model according to the elastic parameters of each indentation point before and after immersion, and calculating the elastic parameter trend of each phase category before and after immersion, the steps include: dividing the phases in the mudstone sample to be evaluated into three types, converting the mixed Gaussian model into a form containing a single phase Gaussian function corresponding to each phase type, a weight coefficient of the phase mechanical properties, a mean parameter and variance parameter information of the phase mechanical properties, wherein the phase categories include clay minerals, carbonate mineral combinations and quartz mineral combinations; using the rewritten mixed Gaussian model, according to the elastic parameters of each indentation point before and after immersion, respectively obtain trend quantities that comprehensively represent the changes in the elastic parameters of all indentation points belonging to the corresponding phase type.
[0010] Preferably, the rewritten Gaussian mixture model is expressed using the following expression:
[0011]
[0012] Where M represents the total number of phase categories, M = 3, m represents the sequence number of each phase category, α m Represents the weight coefficient of each phase category, f m represents the probability density distribution function of each phase category, x n represents the elastic parameters of each indentation point, n represents the serial number of each indentation point, f(x n ) represents the probability density distribution function of the rock sample tested by nanoindentation, μ m , σ m Respectively represent the mean and variance of the Gaussian distribution of each item category.
[0013] Preferably, when performing the nanoindentation test, it includes: determining the indentation parameters of the current test, wherein the indentation parameters include: indentation point array distribution, indentation depth, indentation point spacing, the number of rows and columns of the ballast point array is 15, the indentation depth ranges from 400nm to 500nm, and the indentation point spacing is 20μm; according to the volume representative unit, the working area to be ballasted is selected on the rock sample to be tested, and the nanoindentation test is performed on the working area.
[0014] Preferably, in the step of performing electron microscope scanning on the rock sample, analyzing the distribution and content of each phase in the scanned image, and determining the volume unit representing the microstructure of the rock sample based on this, the steps include: performing SEM-BSE scanning on the rock sample using an electron microscope scanning device to obtain a scanned image characterizing the structural morphology of the mudstone sample to be evaluated; performing energy spectrum EDS analysis on the scanned image to obtain the distribution and content of each phase in the rock sample; according to a preset step size, sequentially intercepting increasing square areas starting from the center of the scanned image to determine the content of each phase corresponding to each square area, and further establishing a relationship curve between the area of the square area and the content of each phase; and determining the square area where the content of each phase tends to be stable as the volume representative unit.
[0015] Preferably, an X-ray diffractometer is used to perform rock mineral composition and content analysis on the ground material of the rock sample.
[0016] Preferably, the step of grinding the mudstone sample to be evaluated includes: grinding the first part of the mudstone sample to be evaluated into powder so that the powder particle size is less than or equal to a preset powder particle size threshold; making the rock sample powder into whole rock slices, natural slices, ethylene glycol saturated slices and heated slices to obtain the object of rock mineral content analysis.
[0017] Preferably, the method further includes: preparing rock samples for electron microscope scanning and nanoindentation testing, wherein, using epoxy resin, the rock samples except the first part of the rock samples in the mudstone rock samples to be evaluated are wrapped, and after the samples are solidified, they are added into a sheet-like cylindrical sample, and the size of the sample is 25 mm in diameter and 5 mm in thickness; grinding and polishing the sample so that one end face of the sample is exposed, and the remaining surfaces are sealed by the epoxy resin, and the upper surface of the sample is parallel to the lower surface, and the roughness of the upper surface and the lower surface is lower than a preset roughness threshold, and the preset roughness threshold is 130 nm.
[0018] Preferably, the method further includes: comparing and analyzing the scanned images of the rock sample before and after immersion, and the elastic parameter trends of each phase category, to obtain analysis results of the influence of each microscopic phase in the shale sample to be evaluated on the degradation of elastic mechanical parameters under the influence of water-rock interaction.
[0019] Compared with the prior art, one or more embodiments of the above scheme may have the following advantages or beneficial effects:
[0020] The present invention proposes a method for obtaining elastic parameters of mudstone before and after water-rock interaction. The method carries out mineral content analysis of mudstone to obtain the content of each mineral component; performs electron microscope scanning and energy spectrum analysis on rock samples, identifies the structure and mineral types of rock samples, and determines the area of representative unit regions; uses epoxy resin to wrap, grind and polish the rock samples, and performs dot matrix nanoindentation test on the rock samples before and after water-rock interaction, and calculates the elastic modulus of each indentation point position according to the load-displacement curve of loading and unloading; uses a mixed Gaussian model to analyze the indentation data to obtain the elastic modulus corresponding to rock clay minerals, carbonate minerals and quartz minerals; finally, uses a multi-scale theoretical homogenization method to determine the macroscopic elastic parameters of the rock samples before and after water-rock interaction. In addition, the present invention can also combine the electron microscope scanning images of rock samples before and after water-rock interaction and the changes in the mechanical parameters of clay minerals to obtain the analysis results of the influence of mudstone water-rock interaction on mechanical parameters. In this way, the present invention can obtain the mechanical parameters of rock samples before and after water-rock interaction without being limited by the size of the rock samples. Furthermore, the rock cuttings discharged from the bottom of the well can be fully utilized to obtain the mechanical characteristic parameters of rock samples in the entire well section before and after water-rock interaction. Compared with the mechanical parameters obtained by conventional triaxial mechanical experiments, they are not affected by defects such as cracks, avoid the shortcomings of mudstone standard rock samples that are not easy to saturate and experimental data divergence, and are more economical and more effective.
[0021] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0023] Figure 1 This is a schematic diagram of the steps of a method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application.
[0024] Figure 2 This is a specific flow chart of the method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application.
[0025] Figure 3 This is a schematic diagram of the principle of the volume representative unit selection process in the method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application.
[0026] Figure 4This is a schematic diagram of the effect of preparing rock samples for electron microscope scanning and nanoindentation testing in the method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application.
[0027] Figure 5 This is a working schematic diagram of the fluid immersion process in the method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application.
[0028] Figure 6 This is a schematic diagram of the load and displacement curve corresponding to a certain indentation point in the method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application. DETAILED DESCRIPTION
[0029] The following will describe the implementation methods of the present invention in detail with reference to the accompanying drawings and embodiments, so that the implementation process of how the present invention applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly. It should be noted that as long as there is no conflict, the various embodiments of the present invention and the various features in the embodiments can be combined with each other, and the technical solutions formed are all within the protection scope of the present invention.
[0030] Rock mechanics parameters are the basic parameters for many construction operations during drilling and development, and are also the basic basis for drilling and completion design and oil production operations such as wellbore stability analysis and hydraulic fracturing. The correctness of rock mechanics parameters is related to the correct formulation of construction plans and the safe implementation of construction. On the other hand, during the drilling and completion process, the bottom rock of the well will inevitably interact with the drilling fluid or fracturing fluid, which will change the mechanical properties of the rock surface. Accurately obtaining the mechanical parameters of the rock before and after the water-rock interaction is of great significance for guiding the drilling and completion design and evaluating the construction effect.
[0031] As a valuable resource, bottom hole cores are usually obtained through coring. The coring operation takes a long time, the coring rate cannot be fully controlled, and the coring operation is generally only for a specific reservoir section, and it is impossible to obtain cores from the entire section. However, the cuttings returned from the annulus during the drilling cycle are relatively sufficient, and cuttings from the entire section can be obtained. If sufficient bottom hole cuttings resources can be used to explore a method to obtain rock mechanical parameters by microscopic testing of small-sized cuttings, it will be of great significance.
[0032] Indentation testing is a simple and efficient means of evaluating the mechanical properties of materials. It can accurately and continuously measure the load-displacement data of the indenter, based on which the relevant mechanical parameters can be easily obtained. It is currently widely used in the study of the mechanical properties of metals, thin film coatings, composite materials and biological tissues. There is a promising prospect for applying indentation testing technology to the acquisition of mechanical parameters of rock materials and the evaluation of water-rock interactions.
[0033] The existing technologies for obtaining the mechanical parameters of rocks before and after water-rock interaction include the following technologies: First, using a rigid flat-bottomed indenter to test the mechanical properties of rocks. The diameter of the indenter in this method reaches 0.5mm to 2mm, and the test size is relatively large. In essence, it is still a macroscopic mechanical test of rocks; Second, using a macroscopic triaxial loading experimental device to test the water-rock interaction. Although this method can control the water temperature, water pressure and axial pressure of the rock sample when it is saturated with water, and can control the saturation time of the rock sample, this method is suitable for rock samples with higher permeability. For mudstone with extremely low permeability, it is difficult to achieve the effect of completely saturating the entire rock sample in a short time; Third, although some schemes can qualitatively measure the degree of damage to rocks caused by cement action, they cannot quantitatively analyze the specific mechanical parameters of rock samples before and after water-rock action.
[0034] At present, the study of the method of obtaining rock mechanical parameters before and after water-rock interaction has achieved certain results, but the experimental methods mostly use macroscopic rock mechanical tests. For shales with microscopic mechanical weak planes such as lamellae, hydration will cause the microscopic mechanical weak planes to evolve and form macroscopic cracks, resulting in core fragmentation, making it impossible to conduct macroscopic mechanical tests after water-rock interaction. Therefore, it is still necessary to explore starting from small-sized rock samples and using microscopic testing methods to conduct rock mechanical parameter research, in order to make up for the difficulties of insufficient macroscopic mechanical test samples and difficult to obtain experimental data, and provide data support for the design of drilling and completion plans.
[0035] Therefore, in order to solve the above technical problems, the present invention proposes a method for obtaining elastic parameters of mudstone before and after water-rock interaction. First, small-sized rock chip samples are ground to prepare glass slides and accurate rock mineral content analysis is carried out on them; the same small-sized rock chip samples are cut, ground and polished, and the rock samples are scanned by SEM-BSE using an electron microscope scanning device to quantitatively analyze the mineral composition of the scanned surface, based on which, the representative unit (REV) of the microstructure volume of the rock sample is selected; then, the water-rock interaction time of the rock sample is designed, and the rock sample is immersed in fluid; then, nanoindentation tests are carried out on the rock samples before and after immersion, and the data point data corresponding to the load-displacement curve of each indentation point are analyzed to obtain microscopic physical phase mechanical parameters (physical phase mechanical parameters of each indentation point), based on which, the mechanical parameters of clay minerals, carbonate minerals and quartz minerals in mudstone are identified using a mixed Gaussian model, and the microscopic physical phase mechanical parameters are cross-scale upgraded in combination with a multi-scale theoretical homogenization method to obtain the mechanical parameters of the rock at the macroscopic scale before and after water-rock interaction. In this way, the process of obtaining the mechanical parameters (especially elastic parameters) of rocks before and after water-rock interaction in the present invention is not limited by the size of the rock sample, and can make full use of the rock cuttings reflected from the bottom of the well to obtain the mechanical parameters of rock samples in the entire well section before and after water-rock interaction, which is highly economical and efficient.
[0036] In addition, the present invention can also compare the scanning electron microscope images of rock samples before and after water-rock interaction, as well as the mechanical parameter differences of clay minerals, carbonate minerals and quartz minerals, analyze the influence of water-rock interaction on the degradation of mechanical parameters of mud shale, and obtain the results of hydration expansion and degradation of mechanical parameters of clay minerals caused by water-rock interaction of mud shale. Thus, data support is provided for the design of formation analysis and drilling and completion schemes.
[0037] Figure 1 This is a schematic diagram of the steps of the method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application. Figure 1 , the method for obtaining elastic parameters of mudstone before and after water-rock interaction (hereinafter referred to as "mudstone water-rock interaction analysis method") described in the present invention is explained. First, step S110 grinds the mudstone sample to be evaluated and conducts accurate rock mineral content analysis. It should be noted here that the mudstone sample to be evaluated selected by the present invention is the rock cuttings discharged from the annulus of the wellbore during the drilling process (drilling cycle process). Since this type of rock cuttings is smaller than the conventional core sampling experiment (the core size in the conventional core sampling experiment is approximately ) The rock samples required are sufficient, but the size is much smaller. Since the rock cuttings are irregular in shape, the larger ones can be selected. Preferably, the length and width of the rock cuttings in the embodiment of the present invention are respectively greater than 10 mm, and the thickness is greater than 2 mm.
[0038] In step S120, the shale rock sample to be evaluated is subjected to an electron microscope scanning test, and the distribution and content of each phase in the scanning image are analyzed. Then, the volume unit representing the microstructure of the rock sample is determined according to the analysis results of the distribution and content of each phase in the image. Then, in step S130, the current shale rock sample to be evaluated is subjected to a nanoindentation test according to the volume representative unit, and the load and displacement curve of the corresponding indentation point is established. Then, the mechanical property parameters (elastic parameters) of each indentation point are calculated using the drawn curve. Next, in step S140, the ballasted rock sample is subjected to fluid immersion, and the rock cuttings sample after immersion is subjected to electron microscope scanning test and nanoindentation test respectively according to the methods described in step S120 and step S130, and the mechanical property parameters (elastic parameters) of each indentation point after immersion are calculated, thereby entering step S150. It should be noted that the fluid immersion process of step S140 is a process of simulating the water-rock interaction between the fluid such as drilling fluid or fracturing fluid and the rock cuttings sample in the well.
[0039] Step S150 uses a mixed Gaussian model to identify the phase category of each indentation point according to the mechanical property parameters (elastic parameters) of each indentation point before and after immersion, and calculates the elastic parameter trend of each phase category before and after immersion. Among them, since the rock fragments contain multiple phases, but the elastic properties of some phase materials are relatively similar, the present invention divides the multiple phases in the rock fragments into three phases of soft, medium and hard according to the mineral hardness type, thereby obtaining clay mineral combinations (soft), carbonate mineral combinations (medium) and quartz mineral combinations (hard). In addition, in step S150, the elastic parameter trend is the most representative elastic parameter data based on the indentation point size level when the elastic parameter description and evaluation of this type of phase is obtained based on the elastic parameters belonging to the same phase category. Therefore, in order to simplify the complexity of the construction process of the macro-model of rock cuttings and rock samples while maintaining the accuracy of the final mechanical characteristic parameters of the rock cuttings and rock samples, the present invention, in step S150, not only classifies the physical phases of the rock cuttings and rock samples, but also further calculates the trend of the most representative elastic parameter data of each physical phase category before and after immersion for the same rock cuttings and rock samples, thereby laying a good foundation for the subsequent step S160.
[0040] Step S160 obtains the macro elastic parameters of the mud shale sample to be evaluated before and after immersion based on the elastic parameter trend data of each phase category before and after immersion obtained in step S150 and the rock mineral content analysis results obtained in step S110. In this way, step S160 constructs the macro mechanical parameter model of the shale sample before and after immersion based on the mineral content analysis results of the rock fragments sample obtained in step S120 and the most representative elastic parameter data based on the indentation point size level of each phase category before and after immersion, thereby obtaining the macro elastic parameters based on the size level of the mud shale sample to be evaluated before and after immersion. Therefore, the present invention proposes a technical solution for obtaining the elastic parameters of shale before and after water-rock interaction based on the microscopic physical phase mechanical characteristics of rocks. The whole process is not limited by the size of the shale sample to be evaluated, nor is it affected by the defect that the micro cracks in the shale will cause the sample to be destroyed under the action of water and rock. The elastic parameters of the mud shale before and after water-rock interaction are obtained conveniently and efficiently.
[0041] It should be noted that the shale water-rock interaction analysis method described in the embodiment of the present invention can obtain the elastic parameters of the mechanical property parameters of the shale before and after the water-rock interaction, and other types of mechanical property parameters obtained using technical concepts similar to the present invention also fall within the protection scope of the present invention.
[0042] Figure 2 This is a specific flow chart of the method for obtaining elastic parameters of shale before and after water-rock interaction in the embodiment of the present application. Figure 1 and Figure 2The shale water-rock interaction analysis method proposed in the present invention is described in detail. First, step S201 prepares a rock sample for analyzing the rock mineral content, thereby entering step S202. In the embodiment of the present invention, in order to ensure the accuracy of subsequent rock mineral content analysis tests, electron microscope scanning tests, and nanoindentation tests, the present invention needs to prepare rock samples required for different tests for the same shale rock cuttings sample to be evaluated.
[0043] In step S201, the obtained shale rock cuttings sample to be evaluated is cut to obtain the first part of the rock sample in the current rock cuttings sample, and the first part of the rock sample is ground into powder so that the powder particle size is less than or equal to the preset powder particle size threshold (wherein the preset powder particle size threshold is preferably 15 μm); then, the rock sample powder is made into whole rock slices, natural slices, ethylene glycol saturated slices and heating slices, so as to obtain a glass slide object for rock mineral content analysis test. Specifically, the rock sample used for rock mineral analysis is to first obtain any part of the shale rock cuttings sample to be evaluated by cutting, and then grind the part into powder. The powder is prepared by sieving step by step using sieves of different mesh sizes, and finally the powder particle size is less than or equal to 15 μm, and the powder is further made into whole rock slices, natural slices, ethylene glycol saturated slices and heating slices to obtain rock mineral analysis samples.
[0044] Step S202 continues to prepare rock samples for electron microscope scanning test and nanoindentation test. In the embodiment of the present invention, the preparation process of the rock sample required for electron microscope scanning test is similar to the preparation process of the rock sample required for nanoindentation test, so the present invention takes the process of preparing the rock sample required for electron microscope scanning test as an example to illustrate step S202. First, the rock samples except the first part of the rock samples in the current mudstone cuttings to be evaluated are wrapped with epoxy resin, and the rock sample samples after being wrapped are solidified into a sheet cylindrical sample, wherein the size of the sheet cylindrical sample is 25mm in diameter and 5mm in thickness; then, the current sheet cylindrical sample is ground and polished, so that one end face of the sample after grinding and polishing is exposed, and the other faces are sealed with epoxy resin, and the upper surface of the current sample is parallel to the lower surface, and the roughness of the upper surface and the lower surface is lower than the preset roughness threshold. Among them, the preset roughness threshold is preferably 130nm. In this way, rock samples for electron microscope scanning test and for nanoindentation test are obtained.
[0045] Figure 4The schematic diagram of the effect of preparing rock samples for electron microscope scanning and nanoindentation testing in the method for obtaining elastic parameters of shale before and after water-rock interaction in an embodiment of the present application is as follows. When preparing rock samples for electron microscope scanning and nanoindentation testing, the rock samples except for the first part of the rock samples in the mudstone cuttings to be evaluated need to be wrapped with epoxy resin, and after the samples solidify, they are formed into a sheet-like cylindrical shape with a diameter of 25 mm and a thickness of 5 mm. The sheet-like cylindrical sample is then finely ground and polished, leaving only one end face of the rock sample exposed, and the rest of the faces are sealed with epoxy resin, so that the upper and lower surfaces of the rock sample are finally parallel, and the surface roughness is less than 130 nm, such as Figure 4 shown.
[0046] After completing the preparation of all the rock samples for the tests, proceed to step S203. Step S203 uses an X-ray diffractometer to perform rock mineral composition and content analysis tests on the rock sample obtained in step S201 for analyzing the rock mineral content. Specifically, the rock mineral composition of the shale rock sample powder obtained in step S201 for analyzing the rock mineral content is analyzed using an X-ray diffractometer. Among them, the shale mineral components (various phases in the shale) include: quartz, potassium feldspar, plagioclase, calcite, dolomite, pyrite, clay minerals, etc. Each mineral component has a different crystal structure, and it is necessary to use an X-ray spectrum to identify the minerals, so as to obtain the content data of each mineral.
[0047] After obtaining the mineral composition and content data of the rock sample, proceed to step S204. Step S204 performs an electron microscope scanning test on the rock cuttings sample for electron microscope scanning test obtained in step S202, analyzes the distribution and content of each phase in the scanning image, and based on this, determines the volume unit representing the stable rock sample microstructure in the scanning image. Specifically, in step S204, first (step S2041) it is necessary to use an electron microscope scanning device to perform SEM-BSE scanning on the rock cuttings sample for electron microscope scanning test obtained in step S202 to obtain a scanning image for characterizing the structural morphology of the mudstone sample to be evaluated. Then (step S2042) perform energy spectrum EDS analysis on the currently obtained scanning image to obtain the distribution and content information of each phase of the rock sample in the image.
[0048] Figure 3 The schematic diagram of the principle of the volume representative unit selection process in the method for obtaining elastic parameters of shale before and after water-rock interaction in the embodiment of the present application. Figure 3As shown, (step S2043) according to the preset square side length expansion step length, with the center of the microscopic phase scanning image obtained in step S2042 after phase distribution and content analysis as the center, square areas with gradually increasing step lengths are intercepted in sequence to determine the distribution and content information of each phase of the rock sample corresponding to the image of each square area, so as to establish a relationship curve between the area of the area and the content of each phase, the horizontal axis of the curve represents the area of the square area, and the vertical axis represents the content data of each phase (different phase data are marked with different colors). In this way, a relationship curve between the area of the area representing different phases and the corresponding phase content is obtained. Finally, (step S2044) the square area where the content data of each phase tends to be stable is determined as a volume representative unit, so that subsequent nanoindentation tests will be performed according to the area of this square area.
[0049] Next, after completing the electron microscope scanning test of the rock sample before immersion, enter step S205. Step S205 performs nanoindentation test on the rock cuttings and rock samples used for nanoindentation test (or completing electron microscope scanning test) obtained in step S202 according to the volume representative unit, so as to establish the load and displacement curve (of each indentation point) of the current nanoindentation test result. Specifically, in step S205, first (step S2051) it is necessary to determine the indentation parameters required for the current nanoindentation test. Among them, the indentation parameters include but are not limited to: indentation point lattice distribution, indentation depth, indentation point spacing and ballast area. The number of rows and columns of the ballast point lattice is 15, the indentation depth range is preferably 400nm to 500nm, and the indentation point spacing is preferably 20μm. Then, (step S2052) according to the volume representative unit determined in step S204, the working area to be ballasted is selected on the rock cuttings sample for nanoindentation test obtained in step S202, and a nanoindentation test consistent with the above indentation parameters is performed on the current working area.
[0050] Figure 6 Schematic diagram of the load and displacement curve corresponding to a certain indentation point in the method for obtaining elastic parameters of shale before and after water-rock interaction in the embodiment of the present application. Finally, (step S2053) after completing the nanoindentation test (before immersion), draw the load and displacement curves of loading and unloading of each indentation point corresponding to the current nanoindentation test process (where each indentation point corresponds to a load and displacement curve), such as Figure 6 It should be noted that since the process of drawing the load and displacement curve is a relatively mature technology in the prior art, it will not be described in detail here.
[0051] Furthermore, the present invention adopts the dot matrix method in the nanoindentation test method, and randomly selects a square area on the rock sample to be tested as the ballast area. The area of the square area is slightly larger than the volume representative unit determined in step S204. The distribution of the ballast matrix points is 15×15, and the indentation depth is between 400nm and 500nm, so that the rigid indenter can be loaded onto the rock sample phase without penetrating the phase, so that the ballast and displacement curve can accurately reflect the mechanical property parameters of the single phase of the mineral. In addition, the spacing between the indentation points is about 20μm to ensure that there is no mutual interference between two adjacent indentation points. In addition, it should be noted that the strain rate needs to be controlled not to exceed 0.05s during the ballast process. -1 , to eliminate the influence of ballasting rate.
[0052] In this way, after completing the nanoindentation test on the rock sample before immersion, enter step S206. Step S206 uses the elastic parameter calculation formula of the indentation point to obtain the elastic parameters at each indentation point in the rock sample before immersion based on the load and displacement curves of each indentation point obtained by the nanoindentation test of the rock sample before immersion (wherein the elastic parameters include but are not limited to the elastic modulus and Poisson's ratio). It should be noted that, in view of the relatively weak sensitivity of the Poisson's ratio to the elastic modulus, in the embodiment of the present invention, the Poisson's ratio value can be given an empirical value. Among them, the elastic parameter calculation formula of the indentation point is expressed by the following expression:
[0053]
[0054] Among them, P represents the load data of the current indentation point, P max represents the maximum load at the current indentation point, h represents the displacement data of the current indentation point, and h max represents the displacement corresponding to the maximum load at the current indentation point, A represents the projected area of the contact area between the indenter head and the rock, S represents the slope of the initial point of the unloading curve in the load-displacement curve of the current indentation point, H represents the rock hardness, and E represents the rock hardness. r represents the reduced elastic modulus, E and ν represent the elastic modulus and Poisson's ratio of the rock sample at the current indentation point, respectively, and E tip , ν tip represent the elastic modulus and Poisson's ratio of the diamond indenter, respectively.
[0055] After obtaining the elastic parameters at each indentation point in the rock sample before the current immersion, the process proceeds to step S207 to immerse the rock sample after the nanoindentation test in step S205 in the fluid. Figure 5 The schematic diagram of the working process of the fluid immersion process in the method for obtaining elastic parameters of shale before and after water-rock interaction in the embodiment of the present application is shown in FIG. In step S207, the fluid immersion process is used to simulate the water-rock interaction of the cuttings and rock samples in the well, and the water-rock interaction time of the rock sample immersion process is designed, such as Figure 5As shown, the ballasted rock sample is immersed in the prepared fluid (in the embodiment of the present invention, the fluid that can be used in the fluid immersion process is consistent with the type and content of the fluid of the water-rock interaction in the well), and the immersion time is recorded. After the set immersion time is reached, the sample is taken out, and the fluid immersion process is completed. The soaked rock cuttings sample is obtained, and then the process enters step S208.
[0056] In step S208, according to the electron microscope scanning test process described in step S204, the rock cuttings sample after immersion obtained in step S207 is subjected to electron microscope scanning test again, and the corresponding volume representative unit is obtained, thereby entering step S209. In step S209, according to the nanoindentation test process described in step S205, after replacing the indentation area of the rock cuttings sample after immersion obtained in step S207, a nanoindentation test is performed to obtain the pressure and displacement curve of each indentation point in the rock cuttings sample after immersion, thereby entering step S210. It should be noted that since the method of step S208 is similar to that of step S204, and the method of step S209 is similar to that of step S205, they are not described in detail here.
[0057] Step S210 obtains the elastic parameters at each indentation point in the rock cuttings sample after immersion (wherein the elastic parameters include but are not limited to elastic modulus and Poisson's ratio) according to the load-displacement curves of each indentation point corresponding to the rock sample after immersion, using the above-mentioned indentation point elastic parameter calculation formula, and then enters step S211.
[0058] Since the dot matrix ballasting of the nanoindentation test cannot guarantee that all the indentation points are completely ballasted onto the rock sample phase, some indentation points will be ballasted onto the interface of different phases, and cannot accurately reflect the mechanical properties of the single phase of the mineral. Therefore, in the embodiment of the present invention, it can be considered that the distribution of the mechanical parameters of each single phase of the mineral obeys the Gaussian distribution, and the rock contains multiple phases. Therefore, the full dot matrix data obeys the mixed Gaussian distribution. Therefore, in step S211, it is necessary to count the elastic modulus data of all indentation points, and use the mixed Gaussian model to classify and identify each phase. Considering that there is no strict boundary between the mechanical parameter values of each microscopic phase, the rock minerals are roughly divided into three types of combinations: soft, medium and hard. The soft mineral combination corresponds to clay minerals, the neutral minerals correspond to carbonate mineral combinations, and the hard minerals correspond to quartz mineral combinations, so that the mixed Gaussian distribution is decomposed into three single Gaussian distributions.
[0059] Step S211 divides the various phases in the mudstone cuttings sample to be evaluated into three types according to the rock hardness. Based on these three phase types, the mixed Gaussian model is converted (rewritten) into a form containing the single-phase Gaussian function corresponding to each phase type, the weight coefficient of the single-phase mechanical property, the mean parameter of the single-phase mechanical property, and the variance parameter information of the single-phase mechanical property, and then enters step S212. These three phase categories are preferably: clay mineral combination corresponding to the soft hardness mineral combination, carbonate mineral combination corresponding to the neutral hardness mineral combination, and quartz mineral combination corresponding to the hard hardness mineral combination. Among them, the rewritten mixed Gaussian model is expressed by the following expression:
[0060]
[0061] In the formula, M represents the total number of phase categories, M=3, m represents the serial number of each phase category, α m Represents the weight coefficient of each phase category, f m represents the probability density distribution function of each phase category, x n represents the elastic parameters of each indentation point, n represents the serial number of each indentation point, f(x n ) represents the probability density distribution function of the rock sample tested by nanoindentation, μ m , σ m Respectively represent the mean and variance of the Gaussian distribution of each item category.
[0062] Step S212 uses the above-rewritten mixed Gaussian model to obtain a trend quantity that comprehensively represents the change of elastic parameters of all indentation points belonging to the same phase type according to the elastic parameters of each indentation point in the rock cuttings sample before immersion, that is, to obtain the trend of elastic parameters of each phase category in the rock cuttings sample before immersion, and obtain a trend quantity that comprehensively represents the change of elastic parameters of all indentation points belonging to the same phase type according to the elastic parameters of each indentation point in the rock cuttings sample after immersion, that is, to obtain the trend of elastic parameters of each phase category in the rock cuttings sample after immersion. Preferably, in an embodiment of the present invention, the elastic parameter trend of each phase category represents the average value (μ) of the elastic parameters of all fracturing points belonging to the current phase category, so as to use the average value as the data based on the fracturing point size level that can best comprehensively evaluate or describe the change trend of elastic parameters of the current phase category among all elastic parameters belonging to the phase category. Thus, the preparation for constructing a macroscopic mineral mechanics characteristic model of a three-dimensional rock sample is completed, and then the process proceeds to step S213.
[0063] Step S213 uses a multi-scale theoretical homogenization method to upgrade the microscopic phase elastic parameters across scales based on the elastic parameter trends of each phase category before and after immersion obtained in step S212, as well as the rock mineral content analysis results, to obtain macroscopic elastic parameters based on the size level of the mudstone sample to be evaluated before and after immersion, thereby converting the elastic parameters corresponding to the nano-scale microscopic objects into the elastic parameters corresponding to the millimeter-level macroscopic rock sample. Specifically, first (step S2131), according to the elastic parameter trend of each phase category before immersion, the phase category volume and shear modulus calculation formula is used to obtain the bulk modulus and shear modulus corresponding to each phase category before immersion from the Poisson's ratio of each phase category before immersion, and according to the elastic parameter trend of each phase category after immersion, the phase category volume and shear modulus calculation formula is used to obtain the bulk modulus and shear modulus of each phase category before immersion from the Poisson's ratio of each phase category after immersion. Among them, the phase category volume and shear modulus calculation formula is expressed by the following expression:
[0064]
[0065] Among them, K J Represents the bulk modulus of each phase category, G J Represents the shear modulus of each phase category, E J represents the trend of elastic parameters of each phase category (preferably, the elastic parameters here represent the trend of elastic modulus), ν J Indicates the elastic parameter trend of each phase category (preferably, the elastic parameter here indicates the Poisson's ratio trend). Among them, the Poisson's ratio trend of the clay mineral combination is preferably 0.3, the Poisson's ratio trend of the carbonate rock mineral combination is preferably 0.2, and the Poisson's ratio trend of the quartz mineral combination is preferably 0.15.
[0066] After obtaining the corresponding bulk modulus and shear modulus of each phase category before and after immersion, (step S2132) needs to be based on the accurate rock mineral content analysis results obtained in step S203, according to the bulk modulus and shear modulus of each phase category before immersion, and use the multi-scale theoretical homogenization method to upgrade the microscopic phase elastic parameters across scales, and obtain the bulk modulus, shear modulus, elastic modulus and Poisson's ratio of the mud shale sample size level to be evaluated before immersion, and according to the bulk modulus and shear modulus of each phase category after immersion, use the multi-scale theoretical homogenization method to upgrade the microscopic phase elastic parameters across scales, and obtain the bulk modulus, shear modulus, elastic modulus and Poisson's ratio of the mud shale sample size level to be evaluated after immersion. Among them, the expression of the multi-scale theoretical homogenization method is as follows:
[0067]
[0068] Among them, Khom It represents the macroscopic bulk modulus of the shale sample before or after immersion, G hom represents the macroscopic shear modulus of the shale sample before or after immersion, K0 and G0 represent the bulk modulus and shear modulus of the clay-based phase minerals before or after immersion, respectively. I , G I represents the bulk modulus and shear modulus of the inclusion phase minerals before or after immersion, respectively; I represents the serial number of the other phase minerals except clay minerals in the mudstone cuttings sample to be evaluated; n represents the total number of other phase minerals except clay minerals in the mudstone cuttings sample to be evaluated; f I Indicates the content data of inclusion phase minerals, E hom , ν hom They represent the macroscopic elastic modulus and Poisson's ratio of the shale sample before or after immersion, respectively.
[0069] It should be noted that the inclusion phase minerals here are other phase minerals in shale rocks except clay minerals, such as quartz, potassium feldspar, plagioclase, calcite, dolomite, pyrite, etc. The content data of these inclusion phase minerals are obtained from the rock mineral content analysis test results of the above step S203. In addition, the corresponding bulk modulus and shear modulus of each inclusion phase mineral are preferably the bulk modulus and shear modulus corresponding to the carbonate rock mineral combination or the quartz mineral combination to which the current inclusion phase mineral belongs, that is, obtained from step S2131.
[0070] In this way, through the above steps S201 to S213, based on the microscopic physical phase mechanical characteristic parameters of the small-sized rock fragments, the macroscopic elastic parameters of the mudstone samples to be evaluated before and after immersion are obtained, thereby obtaining the elastic parameters of the mudstone before and after water-rock interaction.
[0071] In addition, the mudstone water-rock interaction analysis method of the present invention also includes: comparing and analyzing the electron microscope scanning images of the mudstone samples to be evaluated before and after immersion, and comparing and analyzing the elastic parameter trends corresponding to each microscopic phase category, to obtain the analysis results of the influence of each microscopic phase in the mudstone sample to be evaluated on the degradation of elastic mechanical parameters under the influence of water-rock interaction. Specifically, it can be analyzed that each microscopic phase category in the mudstone, under the influence of water-rock interaction, will cause the hydration expansion of clay minerals, thereby deteriorating the mechanical characteristic parameters.
[0072] That is to say, by comparing and analyzing the electron microscope scanning images of rock samples before and after water-rock interaction, it is found that the main microscopic minerals that interact with fluid in shale are expansive clay minerals; at the same time, by comparing the differences in elastic parameters of clay minerals, carbonate minerals and quartz minerals before and after water-rock interaction, it is further explained that the main mechanism for the deterioration of elastic parameters of shale after water-rock interaction is the hydration of clay minerals.
[0073] The embodiment of the present invention proposes a method for obtaining elastic parameters of mudstone before and after water-rock interaction based on the microscopic characteristics of rocks. The method analyzes the mineral content of mudstone to obtain the content of each mineral component; performs electron microscope scanning and energy spectrum analysis on rock samples, identifies the structure and mineral types of rock samples, and determines the area of representative unit regions; uses epoxy resin to wrap, grind and polish the rock samples, and performs dot matrix nanoindentation tests on the rock samples before and after water-rock interaction, and calculates the elastic modulus of each indentation point position according to the load-displacement curve of loading and unloading; uses a mixed Gaussian model to analyze the indentation data to obtain the elastic modulus corresponding to the clay minerals, carbonate minerals and quartz minerals of the rock; finally, a multi-scale theoretical homogenization method is used to determine the macroscopic elastic parameters of the rock samples before and after water-rock interaction. In addition, the present invention can also combine the electron microscope scanning images of the rock samples before and after water-rock interaction and the changes in the mechanical parameters of clay minerals to obtain the analysis results of the influence of mudstone water-rock interaction on the mechanical parameters. In this way, the present invention can obtain the mechanical parameters of rock samples before and after water-rock interaction without being limited by the size of the rock samples. Furthermore, the rock cuttings discharged from the bottom of the well can be fully utilized to obtain the mechanical characteristic parameters of rock samples in the entire well section before and after water-rock interaction. Compared with the mechanical parameters obtained by conventional triaxial mechanical experiments, they are not affected by defects such as cracks, avoid the shortcomings of mudstone standard rock samples that are not easy to saturate and experimental data divergence, and are more economical and more effective.
[0074] Although the embodiments disclosed in the present invention are as above, the above contents are only embodiments adopted for facilitating the understanding of the present invention and are not intended to limit the present invention. Any technician in the technical field to which the present invention belongs can make any modifications and changes in the form and details of the implementation without departing from the spirit and scope disclosed in the present invention, but the patent protection scope of the present invention shall still be subject to the scope defined in the attached claims.
Claims
1. A method for obtaining elastic parameters of shale before and after water-rock interaction, characterized in that: The method comprises: Grind the shale samples to be evaluated and analyze the rock mineral content; Scanning the rock sample with an electron microscope, analyzing the distribution and content of each phase in the scanned image, and based on this, determining the volume unit representing the microstructure of the rock sample, including: scanning the rock sample with an electron microscope scanning device by SEM-BSE to obtain a scanned image representing the structural morphology of the mudstone sample to be evaluated; performing energy spectrum EDS analysis on the scanned image to obtain the distribution and content of each phase in the rock sample; intercepting increasing square areas from the center of the scanned image in sequence according to a preset step length, determining the content of each phase corresponding to each square area, thereby establishing a relationship curve between the area of the square area and the content of each phase; determining the square area where the content of each phase tends to be stable as the volume representative unit; According to the volume representative unit, the rock sample is subjected to nanoindentation test, and the load and displacement curve of each indentation point is established, based on which the elastic parameters of each indentation point are calculated; The ballasted rock sample is immersed in fluid, and the immersed rock sample is sequentially subjected to electron microscope scanning and nanoindentation test, and the elastic parameters of each indentation point after immersion are calculated; According to the elastic parameters of each indentation point before and after immersion, the mixed Gaussian model is used to identify the phase category of each indentation point respectively, and the elastic parameter trend of each phase category before and after immersion is calculated, and the phase category includes clay minerals, carbonate rock mineral assemblages and quartz mineral assemblages; According to the elastic parameter trend, the macro elastic parameters of the shale rock sample to be evaluated before and after immersion are obtained from the rock mineral content analysis results.
2. The method according to claim 1, characterized in that The step of obtaining the macro elastic parameters of the shale rock sample to be evaluated before and after immersion based on the elastic parameter trend and the rock mineral content analysis result includes: According to the elastic parameter trend of each phase category before and after the immersion, the bulk modulus and shear modulus of the corresponding phase category are calculated from the Poisson's ratio of each phase category before and after the immersion; Based on the analysis results of the rock mineral content, according to the bulk modulus and shear modulus of each phase category before and after immersion, the multi-scale theoretical homogenization method is used to upgrade the microscopic phase elastic parameters across scales to obtain the bulk modulus, shear modulus, elastic modulus and Poisson's ratio of the shale sample to be evaluated before and after immersion.
3. The method according to claim 1, characterized in that According to the elastic parameters of each indentation point before and after immersion, the mixed Gaussian model is used to identify the phase category of each indentation point respectively, and the elastic parameter trend of each phase category before and after immersion is calculated, including: The various phases in the shale rock sample to be evaluated are divided into three types, and the mixed Gaussian model is converted into a form containing single phase Gaussian functions corresponding to each phase type, weight coefficients of phase mechanical properties, mean parameters of phase mechanical properties, and variance parameter information; By using the rewritten mixed Gaussian model, according to the elastic parameters of each indentation point before and after immersion, trend quantities comprehensively representing the changes in the elastic parameters of all indentation points belonging to the corresponding phase type are obtained.
4. The method according to claim 3, characterized in that The rewritten Gaussian mixture model is expressed by the following expression: Where M represents the total number of phase categories, M = 3, m represents the sequence number of each phase category, α m Represents the weight coefficient of each phase category, f m represents the probability density distribution function of each phase category, x n represents the elastic parameters of each indentation point, n represents the serial number of each indentation point, f(x n ) represents the probability density distribution function of the rock sample tested by nanoindentation, μ m , σ m Respectively represent the mean and variance of the Gaussian distribution of each item category.
5. The method according to claim 1, characterized in that When performing the nanoindentation test, it includes: Determine the indentation parameters of the current test, wherein the indentation parameters include: indentation point array distribution, indentation depth, and indentation point spacing, the number of rows and columns of the indentation point array is 15, the indentation depth ranges from 400nm to 500nm, and the indentation point spacing is 20μm; According to the volume representative unit, an operating area to be ballasted is selected on the rock sample to be tested, and a nanoindentation test is performed on the operating area.
6. The method according to claim 1, characterized in that The rock sample grind is subjected to rock mineral composition and content analysis test using an X-ray diffractometer.
7. The method according to any one of claims 1 to 6, characterized in that: The grinding step of the shale rock sample to be evaluated includes: Grinding a first portion of the shale rock samples to be evaluated into powder, so that the powder particle size is less than or equal to a preset powder particle size threshold; The rock sample powder is made into whole rock slices, natural slices, ethylene glycol saturated slices and heated slices to obtain the objects for rock mineral content analysis.
8. The method according to claim 7, characterized in that The method further comprises: preparing a rock sample for electron microscope scanning and nanoindentation testing, wherein: Using epoxy resin, wrapping the rock samples except the first part of the rock samples in the mudstone samples to be evaluated, and after the samples are solidified, forming a sheet-like cylindrical sample, the size of the sample is 25 mm in diameter and 5 mm in thickness; The sample is ground and polished so that one end face of the sample is exposed and the other faces are sealed by the epoxy resin, the upper surface of the sample is parallel to the lower surface, and the roughness of the upper surface and the lower surface is lower than a preset roughness threshold, which is 130 nm.
9. The method according to any one of claims 1 to 6, characterized in that: The method further comprises: The scanned images of the rock sample before and after immersion and the elastic parameter trends of each phase category are compared and analyzed to obtain the results of the influence of each microscopic phase in the shale rock sample to be evaluated on the degradation of elastic mechanical parameters under the influence of water-rock interaction.
Citation Information
Patent Citations
Test analysis method for rock erosion depth and deterioration degree of mechanical property
CN109738313A